Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Loyalitas Karyawan Sebagai Pemediasi Pada Karyawan Swasta Di Kota Tangerang - Xena Monica Susanto; Agustinus Priyowidodo (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the effect of leadership style, organizational culture, and job satisfaction on employee performance with employee loyalty as a mediator in private companies in Tangerang City. Effective leadership style, strong organizational culture, and high levels of job satisfaction are considered key factors that can increase employee loyalty, which in turn has a positive impact on employee performance. A quantitative approach was used in this study with a survey method involving a number of employees from various private companies in Tangerang City. Data were collected through structured questionnaires to test the direct and indirect relationships between the variables. Based on the research that has been done, it is found that there is an influence of Leadership Style on Employee Performance with a T-Statistics value of 2.154 and P-Values of 0.032. There is an effect of Organizational Culture on Employee Performance with a T-Statistics value of 2.056 and P-Values of 0.040. There is an effect of Job Satisfaction on Employee Performance with a T-Statistics value of 2.113 and P-Values of 0.035. There is an effect of Employee Loyalty on Employee Performance with a T-Statistics value of 5.239 and P-Values of 0.000. There is an influence of Leadership Style on Employee Loyalty with a T-Statistics value of 2.281 and P-Values of 0.023. There is an effect of Organizational Culture on Employee Loyalty with a T-Statistics value of 3.383 and P-Values of 0.001. There is an effect of Job Satisfaction on Employee Loyalty with a T-Statistics value of 3.116 and P-Values of 0.002. There is an influence of Leadership Style on Employee Performance through Employee Loyalty with a T-Statistics value of 1.986 and P-Values of 0.048. There is an effect of Organizational Culture on Employee Performance through Employee Loyalty with a T-Statistics value of 3.265 and P-Values of 0.001. There is an effect of Job Satisfaction on Employee Performance through Employee Loyalty with a T-Statistics value of 2.314 and P-Values of 0.021.